Harnessing the potential of private sector in nutrition: A prerequisite for meeting goal 2 of Sustainable Development Goals (SDG) 2030 - Dewesh Kumar; Pankaja Ravi Raghav; Pankaj Bhardwaj; Nitesh Kumar (Indian Journal of Community and Family Medicine, 2017)
Private Public partnership (PPP) in nutrition has got huge potential for multisector assistance where industry, government, academia and NGOs can work in harmonization for achieving sustainable development goal related to nutrition. It is imperative to identify viable ways in which local as well as transnational business stakeholders may be better involved to scale up nutrition at the country and global levels. The PPP model in improving nutrition of masses may prove itself to be a cost-efficient and effective implementation of (1) Direct nutrition interventions and (2) Nutrition related interventions. The potential of private sector involvement is immense and can be harnessed in providing micronutrients through food fortification, promoting good dietary practices and therapeutic feeding for malnourished children. Other nutrition domains where private sector can be of great help are agriculture, health, education, economic development and last but not the least disaster preparedness/mitigation efforts.